Pola Kemitraan Komoditi Padi Sawah antara P4S Sri Wijaya dengan Subak Batusangian, Desa Gubug, Kecamatan Tabanan, Kabupaten Tabanan - I MADE SUMA PRIANDIKA; MADE ANTARA; I DEWA AYU SRI YUDHARI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism), 2015)
Abstract Commodity Rice Partnership between P4S Sri Wijaya with Batusangian Subak, Gubug Village, Tabanan District, Tabanan Regency Rice farmers get uncertainty in the sale of production, so the partnership is one solution to get a certainty price. The purpose of research are to determine the partnerships management process that undertaken by Subak Batusangian farmers, knowing the benefits to farmers in terms of both technical and economic, and knowing the constraints faced by farmers P4S Sri Wijaya and Subak Batusangian in partnership. This study uses qualitative and quantitative analysis. The results showed that, partnerships management process undertaken by the farmer goes well. Application of partnership between P4S Sri Wijaya with Subak Batusangian is beneficial for both parties that partner. Based on the analysis of the level of profits earned by the farmers partners R / C is greater than 1, namely with a value of 2.33. The problem that finding on P4S Sriwijaya is difficulty of finding labor at harvest time and the price of rice are unstable for every period. While the constraints faced by farmers in the partnership that is the problem of delay in the companies providing fertilizer for farmers and harvest delays in production. Farmer partnerships with companies should be continued because there are give benefit. The companies should further improve services to farmers, copanies and farmers must be open to each other as well as establishing a good relationship so that in the future more profitable. Keywords: Partnership, rice paddy, farmer, P4S Sri Wijaya